Transcriptome networks identify mechanisms of viral and nonviral asthma exacerbations in children - Altman, Matthew C. (Nat Immunol, 2019)
Respiratory infections are common precursors to asthma exacerbations in children, but molecular immune responses that determine whether and how an infection causes an exacerbation are poorly understood. By using systems-scale network analysis, we identify repertoires of cellular transcriptional pathways that lead to and underlie distinct patterns of asthma exacerbation. Specifically, in both virus-associated and nonviral exacerbations, we demonstrate a set of core exacerbation modules, among which epithelial-associated SMAD3 signaling is upregulated and lymphocyte response pathways are downregulated early in exacerbation, followed by later upregulation of effector pathways including epidermal growth factor receptor signaling, extracellular matrix production, mucus hypersecretion, and eosinophil activation. We show an additional set of multiple inflammatory cell pathways involved in virus-associated exacerbations, in contrast to squamous cell pathways associated with nonviral exacerbations. Our work introduces an in vivo molecular platform to investigate, in a clinical setting, both the mechanisms of disease pathogenesis and therapeutic targets to modify exacerbations.